PTU-138 Central Obesity and Waist Belt Cause Partial Hiatus Hernia and Short Segment Acid Reflux in Healthy Volunteers. (4th June 2013) - Lee, Y Y; Whiting, J G; Robertson, E V; Derakhshan, M H; Wirz, A A; Morrison, D; Weir, A; Smith, D; Kelman, A; McColl, K E L
Abstract : Introduction: Epidemiology demonstrates an association between obesity, hiatus hernia and acid reflux but mechanism is unclear. We have examined the structure and function of the gastro-oesophageal (GO) junction in healthy subjects with and without obesity and the effects of elevating intra-abdominal pressure with belt. Methods: We recruited 8 subjects with normal ( < 94 cm males < 80 cm females) and 8 with increased ( > 102 cm males > 88 cm females) waist circumference, matched for age and gender. To allow accurate monitoring of location of the GO junction and its proximal movement during TLOSRs, a magnet (2x1 mm) was endoscopically clipped to the SCJ. Combined assembly of locator probe, high-resolution pH catheter and slimline manometer was passed nasally. After a standard meal, recording seated upright was continued for an hour. A waist belt was applied on a separate day throughout the entire recording. The effect of obesity was assessed by comparing obese vs. non-obese, both without belt. The effect of belt was assessed by comparing entire group with and without belt. The effect of belt in obesity was assessed by comparing belt-on vs. off in obese subjects. All results were in mean (SEM). Results: Location of the SCJ ( P = 0.006) and pH step-down ( P = 0.01) were displaced proximally in obese vs. non-obese but the diaphragm was not displaced as reflected by peak LOS pressure (pLOS) and pressure inversion point (PIP) (Figure). With belt-on vs. off, there was similarly proximal displacement of SCJ and pH step-down and also of the diaphragm ( P = 0.003) and LOS (upper and lower border, P = 0.01 and 0.03 respectively). In obese subjects with belt-on vs. off, there was proximal displacement of SCJ, pH step-down and diaphragm. There was marked proximal migration of SCJ during TLOSRs with its magnitude being less in obese vs. non-obese (4.2 vs. 6.8 cm, P = 0.04) and belt-on vs. off (3.9 vs. 5.5 cm, P = 0.01), consistent with its resting position being already proximally displaced. At traditional site (5 cm above LOS), the mean % time pH < 4 was minimal (0 – 0.5%) in all studied groups, however, acid exposure above the SCJ but below upper border LOS was increased in belt-on vs. off (6.2% vs. 1.6%, P = 0.01) and in obesity with belt-on vs. off (9.7% vs. 3.0%, P = 0.04) but not obese vs. non-obese ( P = 0.2). Conclusion: Our findings indicate that in asymptomatic volunteers, central obesity and waist belt cause partial hiatus herniation and that waist belt also causes short segment reflux. Disclosure of Interest: None Declared